Is there still a place for erythrocyte sedimentation rate and C-reactive protein in systemic lupus erythematosus?. (October 2016) - Dima, A; Opris, D; Jurcut, C; Baicus, C
The inflammatory response during systemic lupus erythematosus (SLE) flares is known to be atypical, characterized by a disproportionately lower C-reactive protein (CRP) elevation when compared with erythrocyte sedimentation rate (ESR). Thus, in these patients, the analysis of inflammatory markers might be challenging in daily clinical practice. Clinicians need frequently to distinguish lupus reactivations and infectious conditions, and the significance of ESR and CRP seems to be different. Even though a non-specific marker of inflammation, ESR utility in SLE should not be neglected and it appears to be a useful biomarker for SLE activity assessment. Describing a specific cut-off for ESR in SLE is important for patients' follow-up, and levels up to 25–30 mm/h have been proposed as an upper limit of the normal range. Regarding CRP, even though higher baseline levels are described in SLE when compared with controls, including in remission periods, its response during flares seems to be incomplete and not always correlated with disease activity; while CRP values greater than 10 mg/l could be indicative for severe flares, when there is no serositis or arthritis, higher CRP levels above 50–60 mg/l may be associated with infection.